A Surface Modification Strategy Towards Reversible Na-ion Intercalation on Graphitic Carbon Using Fluorinated Few-Layer Graphene. Issue 10 (1st October 2022) - Sarbapalli, Dipobrato; Lin, Yu-Hsiu; Stafford, Sean; Son, Jangyup; Mishra, Abhiroop; Hui, Jingshu; Nijamudheen, A; Romo, Adolfo I. B.; Gossage, Zachary T.; van der Zande, Arend M.; Mendoza-Cortes, Jose L.; Rodríguez-López, Joaquín
Abstract : Na-ion batteries (NIBs) are proposed as a promising candidate for beyond Li-ion chemistries, however, a key challenge associated with NIBs is the inability to achieve intercalation in graphite anodes. This phenomenon has been investigated and is believed to arise due to the thermodynamic instability of Na-intercalated graphite. We have recently demonstrated theoretical calculations showing it is possible to achieve thermodynamically stable Na-intercalated graphene structures with a fluorine surface modifier. Here, we present experimental evidence that Na + intercalation is indeed possible in fluorinated few-layer graphene (F-FLG) structures using cyclic voltammetry (CV), ion-sensitive scanning electrochemical microscopy (SECM) and in situ Raman spectroscopy. SECM and Raman spectroscopy confirmed Na + intercalation in F-FLG, while CV measurements allowed us to quantify Na-intercalated F-FLG stoichiometries around NaC14–18 . These stoichiometries are higher than the previously reported values of NaC186 in graphite. Our experiments revealed that reversible Na + ion intercalation also requires a pre-formed Li-based SEI in addition to the surface fluorination, thereby highlighting the critical role of SEI in controlling ion-transfer kinetics in alkali-ion batteries. In summary, our findings highlight the use of surface modification and careful study of electrode-electrolyte interfaces and interphases as an enabling strategy for NIBs.